An update on oral manifestations of systemic disorders in dogs and cats - Dosenberry, Claire; Arzi, Boaz; Palm, Carrie; Vapniarsky, Natalia; Soltero-Rivera, Maria (Frontiers in Veterinary Science, 2025)
Oral lesions are common in dogs and cats, and determining the underlying etiology of these lesions can be challenging. A wide range of systemic ailments may lead to lesions in the oral cavity, including immune-mediated diseases, adverse drug reactions, viral and bacterial infections, and metabolic and autoimmune diseases. A complete history and thorough physical examination (including a fundic examination) should be obtained in affected patients. It is critical to perform a detailed oral examination, which in some patients may need to be performed under sedation or general anesthesia. Tailored diagnostic plans and a multidisciplinary approach are necessary to fully characterize co-morbid disorders in affected patients. This narrative review aims to aid veterinarians in recognizing oral manifestations of systemic disorders based on the most recent reports and available research.